The Effect of Using Role-Play Method on Students’ Speaking Skills in the Tenth Grade of SMA Pembangunan Laboratorium UNP - Farisyah Safitri; Carbiriena Solusia (Journal of English Language Teaching, 2023)
This study aimed to identify whether using role-play in teaching English effectively improves the students' English Speaking skills and to analyze the significant difference between the tenth-grade students of SMA Pembangunan Laboratorium UNP who were taught by using the role-play method and those who were taught without using the role-play method. The researcher conducted the research with tenth-grade students of SMA Pembangunan Laboratorium UNP in the academic year 2022/2023, using purposive sampling, X.E class, and X.D was the sample. Experimental research is used in this study by using a quantitative approach and the semi-scripted role-play method. The role-play method effectively improves the students’ English Speaking skills and there is a significant difference between the tenth-grade students improving speaking skills between those taught using the role-play method and those taught without using the role-play method in SMA Pembangunan Laboratorium UNP. Teachers need to be able to select appropriate instructional strategies such as using the method of role-play so that students can express themselves and talk more freely without feeling fearful or lacking in self-confidence.